Comparison of an Innovative Rehabilitation, Combining Reduced Conventional Rehabilitation with Balneotherapy, and a Conventional Rehabilitation after Anterior Cruciate Ligament Reconstruction in Athletes - Peultier-Celli, Laetitia; Mainard, Didier; Wein, Frank; Paris, Nicolas; Boisseau, Patrick; Ferry, Alexandre; Gueguen, René; Chary-Valckenaere, Isabelle; Paysant, Jean; Perrin, Philippe (Frontiers in Surgery, 2017)
Background: Instability of the knee, related to anterior cruciate ligament injury, is treated by surgical reconstruction. During recovery, a loss of proprioceptive input can have a significant impact. Few studies have evaluated the benefits of rehabilitation of the knee in aquatic environment on functional outcomes. Objective: This study aimed to compare an innovative rehabilitation protocol combining reduced conventional rehabilitation with aquatic rehabilitation, with a conventional rehabilitation, according to the National French Health Authority, in terms of kinetics, development of proprioceptive skills and functional improvement of the knee. Methods: 67 patients, who were amateur or professional athletes, were randomized into two groups: 35 patients followed the conventional rehabilitation protocol (Gr1) and 32 patients followed the innovative rehabilitation protocol (Gr2). Patients were evaluated before surgery, and at two weeks, one, two and six months after surgery using posturography, and evaluation of muscular strength, walking performance and proprioception. This study is multicenter, prospective, randomized, and controlled with a group of patients following conventional rehabilitation (level of evidence I). Results: For the same quality of postural control, Gr2 relied more on somesthesia than Gr1 at six months. The affected side had an impact on postural control and in particular on the preoperative lateralization, at two weeks and at one month. Lateralization depended on the affected knee, with less important lateralization in Gr2 preoperatively and at one month. The quadriceps muscular strength was higher in Gr2 than in Gr1 at two and six months and muscle strength of the external hamstring was greater in Gr2 than in Gr1 at six months. The isokinetic test showed a greater quadriceps muscular strength in Gr2. Gr2 showed a greater walking distance than Gr1 at one month. Gr2 showed an improvement in the proprioceptive capacities of the operated limb in flexion for the first two months. Conclusions: The effectiveness of the innovative rehabilitation program permits faster recovery, allowing for an earlier return to social, sporting and professional activities. Faster retrieval of knee function following aquatic rehabilitation would prevent both short-term risk of lesions of the contralateral limb due to overcompensation and long-term risk of surgery due to osteoarthritis.